Eksplorasi Aplikasi Arabic Muslim Adventure Berdasarkan Hierarchy of Design Don Norman - Fathanah, Isma; Al Farisi, Mohamad Zaka; Maulani, Hikmah (Al-Lisan: Jurnal Bahasa, 2025)
Background: This research discusses the Arabic Muslim Adventure application, an interactive app designed to help students learn Arabic through a game-based learning approach. The main issue explored is how this application affects students' functional and emotional engagement. Aims: This research aims to explore the extent to which Don Norman's hierarchy of design is applied in the user-centred AMA application from functional and emotional aspects. Methods: The research method used a descriptive qualitative approach. Data sources were obtained from field observations and interviews with participants. Sampling was carried out using a non-probability sampling technique with purposive sampling based on gender. The participants in this research were eight elementary school students. The data collection technique was carried out through two stages, namely observations and interviews. The data analysis process through: data display, data verification, and conclusion drawing. Results: AMA is easy to use because of the familiar icons and useful to help understand Arabic vocabulary. The AMA application has an Islamic cultural identity and attractive visuals that successfully increase learning motivation. Some improvements are proposed, such as adding notifications on the charades game and clearer explanations in the mufradat section. This application successfully combines functional and emotional aspects that create positive responses. Implications: This research is expected to provide new insights into the importance of a user-centred design approach in the development of educational applications, especially in the context of Arabic language education.